EFEKTIFITAS MODEL ACTIVE DEBATE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI SMAN 9 PONTIANAK - Robayah, Siti; Tampubolon, Budiman; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The purpose of this research is to determine the effect of the application of the Active Debate learning model on class XI geography learning in SMA Negeri 9 Pontianak. The research method used was quasi-experimental (Quasi Experimental), with quantitative research forms. The research data source is population of class XI IPS with sample class XI IPS 4 as the experimental class and class XI IPS 1 as the control class. Data collection techniques consisting of: measurement techniques, while the data collection tool used is a written test in the form of multiple choice totaling 50 questions. Based on statistical calculations the average learning outcomes of the control class is 80.97 and the average learning outcomes of the experimental class is 84.62. The results of learning the hypothesis test using the t-test were tarithnetic 6.2076 and ttable (? = 5% where dk -2 = 34 + 34-2 = 66) amounted to 1.997 so which means tarithnetic (6.2076)> ttable (1.997), then, Ha is accepted . From the results of the calculation of the effect size (ES) obtained an effect size of 0.716 in the medium category. From these explanations, it can be concluded that there is an influence on the application of active debate models in geography learning on the learning outcomes of students of class XI IPS in SMA Negeri 9 Pontianak. Keywords: Active Debate Learning Model, Geography Learning, Learning Outcomes